The Impact of Instagram Social Media Marketing Activities on Customer Engagement for a Product - Dea Eka Andriani; Devina Apriliyanti; Jeremia Joel Sutjianto; Meili (Lentera Jurnal Pengabdian Masyarakat, 2026)
This study aims to examine the impact of Instagram Social Media Marketing Activities (SMMA) and Visual Communication on Customer Engagement and Purchase Intention among Instagram users. The research is based on Engagement Theory and the Stimulus–Organism–Response (S-O-R) framework, where Visual Communication and SMMA act as stimuli, Customer Engagement acts as the organism, and Purchase Intention acts as the response. A quantitative research design with a causal approach was applied in this study. Data were collected through an online questionnaire distributed to active Instagram users who follow brand accounts and interact with brand-related content. A total of 50 valid responses were analyzed using IBM SPSS Statistics. The analysis methods included descriptive statistics, validity and reliability tests, classical assumption tests, multiple regression analysis, and mediation analysis. The findings reveal that Visual Communication and Customer Engagement significantly influence Purchase Intention, while Social Media Marketing Activities (SMMA) do not significantly affect either Customer Engagement or Purchase Intention. In addition, Customer Engagement does not mediate the relationship between Visual Communication, SMMA, and Purchase Intention. The study concludes that visual appeal and emotional connection are more influential in driving purchase intention compared to the intensity of social media marketing activities. These findings provide practical implications for businesses to focus more on high-quality visual content and meaningful customer relationships in digital marketing strategies.